2022
DOI: 10.3389/fcvm.2022.854757
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Feasibility of Rotational Atherectomy for Retrograde Recanalization of Chronically Occluded Coronary Arteries

Abstract: ObjectiveTo evaluate the safety and feasibility of rotational atherectomy (RA) in retrograde chronic total occlusion percutaneous coronary intervention (CTO-PCI) by analyzing immediate and long-term outcomes.BackgroundRecent evidence supports the safety and feasibility of RA in CTO-PCI. However, few studies have focused on the use of RA in a retrograde approach to percutaneous revascularization of chronic total occlusion (CTO) lesions and information on long-term outcomes is lacking.MethodsA total of 329 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…Our results indicate that both RA and conventional stenting are viable treatment options for CTO lesions with comparable safety and efficacy profiles. Despite specific differences in procedural qualities and outcomes, for example, procedural time and fluoroscopy time, the two gatherings accomplished comparative paces of procedural achievement and difficulty rates (9,10). Besides, the adequacy measures, including the recurrence of periprocedural myocardial dead tissue (MI), top troponin level, and mean change in left ventricular discharge portion (LVEF), were comparative between the two gatherings, recommending that the two techniques are successful in improving myocardial perfusion and capability in patients with CTO sores (11).…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate that both RA and conventional stenting are viable treatment options for CTO lesions with comparable safety and efficacy profiles. Despite specific differences in procedural qualities and outcomes, for example, procedural time and fluoroscopy time, the two gatherings accomplished comparative paces of procedural achievement and difficulty rates (9,10). Besides, the adequacy measures, including the recurrence of periprocedural myocardial dead tissue (MI), top troponin level, and mean change in left ventricular discharge portion (LVEF), were comparative between the two gatherings, recommending that the two techniques are successful in improving myocardial perfusion and capability in patients with CTO sores (11).…”
Section: Discussionmentioning
confidence: 99%
“…13 Các tác giả Ma. Y và cộng sự 14 , Wang, J và cộng sự 15 thực hiện RA cho tổn thương CTO đã cho thấy được tính an toàn, hiệu quả trong ngắn hạn và dài hạn tương tự như nhóm tổn thương CTO không RA. Như vậy, RA là một công cụ có thể được lựa chọn để can thiệp những tổn thương CTO mà bóng nong thông thường không thể nong được tổn thương.…”
Section: đặC đIểm Tổn Thương độNg Mạch Vành Của đốI Tượng Nghiên Cứu ...unclassified
“…In our previous studies, we have identified age, diabetes, renal insufficiency, ACS, cardiogenic shock, and residual Syntax score as prognostic factors for short and intermediate outcomes (16,17). Despite several studies having reported on the feasibility of rotablation for CTO lesions (4,(18)(19)(20)(21)(22)(23)(24)(25), only two of them compared RA for CTO vs. RA for non-CTO lesions (26,27). For the studies that compared RA for CTO with non-CTO lesions, none of them was analyzed after correcting for confounding factors.…”
Section: Introductionmentioning
confidence: 99%